A systematic review of contemporary phase I trials in patients with recurrent/metastatic head and neck cancer - V.G. Espeli; A. Gomez; P. Balermpas; G. Treglia; A. Stathis (Oral Oncology Reports)
We performed a systematic review of phase I trials specifically conducted for patients with head and neck squamous cell carcinoma published between January 1, 2008 and August 31, 2023. PubMed and Cochrane Library databases were searched using a combination of terms: “((head and neck) OR (head & neck)) AND ((cancer*) OR (tumor*) OR (tumour*) OR (neoplasm*) OR (carcinoma*) OR (malignan*)) AND ((phase 1) OR (phase I))''to identify phase I dose-finding trials including a majority of lymphoma patients.Eighty-five trials (H&N patients N = 1714) were included. Among them, 53 trials complying with inclusion/exclusion criteria and were included in the current analysis: 32 (60 %) enrolled only patients with head and neck cancer, while 21 (40 %) included also patients with other solid tumors.The median rate of grade 3-4 adverse events was 41 %. With regards to clinical activity, the median response rate (RR) was 16 %, which is in line with the usually reported rate for phase I trials enrolling unselected populations of patients with solid tumors.